Enforcing International Law in the South China Sea: Can Southeast Asia Keep China in Check? - Beckley, Michael (2016)
Contrary to the predictions of many analysts, China is hardly poised to establish naval domination over the South China Sea. The states of Southeast Asia hold significant advantages vis-à-vis China in the maritime domain, though the Philippines remains a weak link.